Status of Employment Among Tamangs and Non-Tamangs Women in Sindhupalchowk District - Dulal, Tulasa Devi (KMC Research Journal, 2019)
This paper tries to highlight the women’s working status in previous time to some changing status these days in Sinhupalchowk District. In the previous time women have to do all manual work, women reserve the grain, tend to the livestock, grow the vegetable in the kitchen garden, transplant the saplings at the start of the cropping season and than again reap, thresh and clean the harvest. Such activities are not restricted to the village economy alone; women are also equally involved in other development work of their community these days. The family work could be defined as the total volume of physical and mental labour performed for the maintenance of a family. It incorporate all the endeavors applied for the person him/herself and for others. Indeed, the family work in total should be termed as the collective responsibility of all the members of family. However the burden of family work is usually greater for the women and for those people living in the marginalized economy of the household. The CNAS collected data suffices the ground to conclude that the women in Sindhupalchowk have miserable life .But now-days some women are changing their employment to government service and foreign employment.